Motivation for Achievement and Relationship to Distance Teaching during the Corona Pandemic by Kindergarten Teachers in Makkah-Al-Mukarrama - Alsharif, Sumayyah Mubarak; Akram, Hadeel Abdullah (Journal of Educational and Psychological Sciences, 2025)
The aim of the study is to identify the level of achievement motivation and its relationship to distance teaching during the Corona pandemic among kindergarten teachers in the city of Makkah Al-Mukarramah. The study community consisted of (567) female teachers in government schools, and (175) female teachers in private schools, The study sample included (175) kindergarten teachers, where the researcher followed the mixed method. Interviews were also conducted with (8) kindergarten teachers. The results of the study indicated that the level of achievement motivation for kindergarten teachers in Makkah Al-Mukarramah is very high, and there are no statistically significant differences in the average degrees of achievement motivation for kindergarten teachers due to the variable (labor sector, monthly salary, experience). However, there is a difference in the traditional methods of teaching in the presence and distance teaching from the point of view of kindergarten teachers, through the results of qualitative data. The views of kindergarten teachers also varied on the extent to which kindergarten children interact with distance e-learning during the Corona pandemic. The most prominent obstacles faced by kindergarten teachers during remote teaching within "Rawdaty" platform during the Corona pandemic were also identified; in addition, the most prominent proposed solutions to overcome the obstacles faced by kindergarten teachers while teaching remotely through “Rawdaty” platform during the Corona pandemic were also identified. Based on the results of the study, the researcher reached a number of recommendations, the most important of which are: prepare programs and training courses for kindergarten teachers to use distance e-learning, prepare and develop new innovative programs and platforms that facilitate the educational process.
Keywords: Achievement Motivation; Distance Teaching; Distance E-Learning; Kindergarten Teachers; Corona Pandemic